Artificial Intelligence in the Public Sector : Maximizing Opportunities, Managing Risks - World Bank (World Bank, Washington, DC, 2021)
The paper curate’s knowledge residing in public documents and aims to distill lessons learned on how to adopt and use AI as part of a public sector modernization strategy. The paper’s primary scope is on governance-related aspects. Chapter two elaborates on the opportunities being availed by governmentsaround the world using AI. These opportunities should be availed while managing associated risks, which are discussed in chapter three. For maximizing opportunities and managing risks, governments need to adopt AI ethical principles and institutional arrangements, discussed in chapter four. Chapter five discusses the ethical dimensions that need a broader policy response at the national level. Chapter six enumerates the building blocks necessary for a successful long-term AI strategy. The appendices contain information for practitioners. Appendix A provides technical information and additional resources for further support, and Appendix B highlights solutions that rely on AI for improvements in efficiency, scientific analysis, and prediction within the disciplines. To fully comprehend the impact that AI might have on governments, it is necessary to develop a solid understanding of key AI concepts. The paper does not offer in-depth coverage of work in specific sectors. The findings in the paper were validated through interviews with industry experts. Special efforts have been made to ensure the architectural design approaches discussed in the paper incorporate the best industry knowledge. The paper goes to great lengths to maintain a practical approach, with ‘handson’ examples of architectures and applications.